Association of a placental Interleukin-6 genetic variant (rs1800796) with DNA methylation, gene expression and risk of acute chorioamnionitis - Chaini Konwar; Giulia F. Del Gobbo; Jefferson Terry; Wendy P. Robinson (BMC, 2019)
Abstract Background Acute chorioamnionitis (aCA), inflammation of the placenta and fetal membranes, is a frequently reported lesion in preterm deliveries. Genetic variants in innate immune system genes such as Interleukin-6 (IL6) may contribute to the placenta's inflammatory response, thus predisposing some pregnancies to aCA. These genetic variants may modulate molecular processes such as DNA methylation and gene expression, and in turn might affect susceptibility to aCA. Currently, there is remarkably little research on the role of fetal (placental) genetic variation in aCA. We aimed to explore the associations between genetic variants in candidate immune-system genes and susceptibility towards inflammatory responses in the placenta, which is linked to a strong inflammatory response in the newborn. Methods DNA samples from 269 placentas (72 aCA cases, 197 non-aCA cases) were collected for this study. Samples were genotyped at 55 ancestry informative markers (AIMs) and 16 additional single nucleotide polymorphisms (SNPs) in 12 candidate innate immune system genes using the Sequenom iPLEX Gold Assay. Publicly available datasets were used to obtain DNA methylation (GSE100197, GSE74738, GSE115508, GSE44667, GSE98224) and gene expression data (GSE44711, GSE98224). Results Differences in IL6 placental allele frequencies were associated with aCA (rs1800796, p = 0.04) with the CC genotype specifically implicated (OR = 3.1; p = 0.02). In a subset of the placental samples (n = 67; chorionic villi), we showed that the IL6 SNP (rs1800796) was associated with differential DNA methylation in five IL6-related CpG sites (cg01770232, cg02335517, cg07998387, cg13104385, and cg0526589), where individuals with a CC genotype showed higher DNA methylation levels than individuals carrying the GG genotype. Using two publicly available datasets, we observed that the DNA methylation levels at cg01770232 negatively correlated with IL6 gene expression in the placenta (r = − 0.67, p < 0.004; r = − 0.56, p < 2.937e-05). Conclusions We demonstrated that the minor C allele at the IL6 SNP (rs1800796), which is largely limited to East Asian populations, is associated with the presence of aCA. This SNP was associated with increased DNA methylation at a nearby MEPC2 binding site, which was also associated with decreased expression of IL6 in the placenta. Decreased expression of IL6 may increase vulnerability to microbial infection. Additional studies are required to confirm this association in Asian populations with larger sample sizes.